Case Report: Consistent disease manifestations with a staggered time course in two identical twins affected by adenosine deaminase 2 deficiency - Barzaghi, Federica; Cicalese, Maria Pia; Zoccolillo, Matteo; Brigida, Immacolata; Barcella, Matteo; Merelli, Ivan; Sartirana, Claudia; Zanussi, Monica; Calbi, Valeria; Bernardo, Maria Ester; Tucci, Francesca; Migliavacca, Maddalena; et al. (Frontiers in Immunology, 2022)
Deficiency of adenosine deaminase 2 (DADA2) is an autosomal recessive disease associated with a highly variable clinical presentation, including vasculitis, immunodeficiency, and hematologic manifestations, potentially progressing over time. The present study describes the long-term evolution of the immuno-hematological features and therapeutic challenge of two identical adult twin sisters affected by DADA2. The absence of plasmatic adenosine deaminase 2 (ADA2) activity in both twins suggested the diagnosis of DADA2, then confirmed by genetic analysis. Exon sequencing revealed a missense (p.Leu188Pro) mutation on the paternal ADA2 allele. In contrast, whole genome sequencing identified an unreported deletion (IVS6_IVS7del*) on the maternal allele predicted to produce a transcript missing exon 7. The patients experienced the disease onset during childhood with early strokes (Patient 1 at two years, Patient 2 at eight years of age), subsequently followed by other shared DADA2-associated features, including neutropenia, hypogammaglobulinemia, reduced switched memory B cells, inverted CD4:CD8 ratio, increased naïve T cells, reduced follicular regulatory T cells, the almost complete absence of NK cells, T-large granular cell leukemia, and osteoporosis. Disease evolution differed: clinical manifestations presented several years earlier and were more pronounced in Patient 1 than in Patient 2. Due to G-CSF refractory life-threatening neutropenia, Patient 1 successfully underwent an urgent hematopoietic stem cell transplantation (HSCT) from a 9/10 matched unrelated donor. Patient 2 experienced a similar, although delayed, disease evolution and is currently on anti-TNF therapy and anti-infectious prophylaxis. The unique cases confirmed that heterozygous patients with null ADA2 activity deserve deep investigation for possible structural variants on a single allele. Moreover, this report emphasizes the importance of timely recognizing DADA2 at the onset to allow adequate follow-up and detection of disease progression. Finally, the therapeutic management in these identical twins raises significant concerns as they share a similar phenotype, with a delayed but almost predictable disease evolution in one of them, who could benefit from a prompt definitive treatment like elective allogeneic HSCT. Additional data are required to assess whether the absence of enzymatic activity at diagnosis is associated with hematological involvement and is also predictive of bone marrow dysfunction, encouraging early HSCT to improve functional outcomes.